Optimal energy mix in relation to multi-criteria decision-making (MCDM), review and further research directions - Mrkić-Bosančić, Maja; Vasković , Srđan; Gvero, Petar; Krunić, Gojko (Decision Making: Applications in Management and Engineering, 2023)
The need for a transition to a society that will meet its energy needs from local resources and with minimal negative environmental impact is no longer presented as an option but as a necessity. Energy resources are limited, and it is necessary to ensure that they are properly used and managed in a sustainable manner. Optimal redistribution of energy supply from different energy generation and distribution options to end users within the local community is called the energy mix. What sets itself the task is to find this way of sustainable use of all available energy and energy types from local communities, different regions to the entire country. This is not a simple task, because it includes many variables that must all be considered. Therefore, it is necessary to classify and define universal criteria (sustainability), which describe ways of supplying energy and energy in a particular locality. The criteria mainly describe energy needs, availability of energy resources, existing technologies, economic and environmental indicators, qualitative and quantitative values of different energy supply options. This paper aims to review the state of play in optimal energy mix research in relation to the local community. Also, this paper provides an overview and importance of the application of MCDM methods in this area. As a way out, in this paper we propose conclusions, directions and research opportunities in the field of seeking the optimal energy mix supply for local community, region or state, connected to the importance MCDM tools.